2022
DOI: 10.2147/jhc.s376210
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Autophagy Response in Hepatocellular Carcinomas Enriches Glypican-3 in Exosomes, Not in the Microvesicles

Abstract: Background and Aim HCC development in liver cirrhosis is associated with impaired autophagy leading to increased production of extracellular vesicles (EVs) including exosomes and microvesicles. The goal of the study is to determine which of these particles is primarily involved in releasing of HCC-specific biomarker glypican-3 (GPC3) when autophagy is impaired. Methods Streptavidin-coated magnetic beads were coupled with either biotinylated CD63 or Annexin A1 antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…33 We demonstrated HCC development in the cirrhotic liver is accompanied by impaired autophagy and increased EV shedding (microvesicle and exosomes). [34][35][36][37] This data is consistent with reports from other researchers indicating that cancer cells secrete significantly higher amounts of exosomes and microvesicles than normal cells, which could be harnessed as a minimally invasive biomarker for cancer diagnosis. 38,39 However, isolating and quantifying organ-specific exosomes has created a significant hurdle to establishing causal relationships between EV biology and underlying disease.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…33 We demonstrated HCC development in the cirrhotic liver is accompanied by impaired autophagy and increased EV shedding (microvesicle and exosomes). [34][35][36][37] This data is consistent with reports from other researchers indicating that cancer cells secrete significantly higher amounts of exosomes and microvesicles than normal cells, which could be harnessed as a minimally invasive biomarker for cancer diagnosis. 38,39 However, isolating and quantifying organ-specific exosomes has created a significant hurdle to establishing causal relationships between EV biology and underlying disease.…”
Section: Introductionsupporting
confidence: 91%
“…The performance of HCC exosome quantification by F-NTA in the same set of samples was compared with the magnetic bead assay described by our group previously. 37 The immunomagnetic beads were prepared by mixing streptavidin-conjugated magnetic beads with biotinylated CD63 antibodies, followed by blocking and incubation directly with the serum for EV capture. This assay principle is that serum exosomes immobilized onto beads reacted either with PE-labeled AFP or PE-labeled GPC3 or in a combination of both antibodies ( Figure 9A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2C). Considering the prevalence of GPC3 as a biomarker and therapeutic target in HCC [32,33], its presence in the top most candidate genes was anticipated, confirming the validity of our approach. However, to ensure the specificity of markers for minimizing therapy-related toxicity, the expression of most favorable HCC marker genes was checked in HCC samples as well as vital organs (Fig.…”
Section: Resultssupporting
confidence: 65%
“…The development of HCC is linked to compromised autophagy, resulting in the increased production of extracellular vesicles, such as exosomes and microvesicles [56,57]. Recent studies revealed complex associations between exosome formation and autophagy, where autophagy machinery can either boost or hinder EV secretion [58]. The modulation of autophagy can significantly influence both the quantity and content of EVs, consequently playing a pivotal role in determining whether autophagy modulators have pro-tumorigenic or anticancer effects.…”
Section: Evs In Hepatocellular Carcinomamentioning
confidence: 99%